Evaluation of the Raw Material Purchasing Accounting System at PT Varia Usaha Beton - Finanda Salsahira; Oryza Tannar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The rapid growth of the business world is forcing companies to adopt automation and efficiency to survive and compete. PT. Varia Usaha Beton, a concrete manufacturer, relies heavily on an accounting system for raw material purchasing to ensure efficient operations. The purpose of this research is to evaluate the company's raw material purchasing accounting system, identify problems and recommend improvements. The research method used is descriptive and qualitative with a case study approach. Primary data was obtained through interviews and observations, while secondary data was obtained through company documents. The research results show that the system works well and supports cost control, inventory management and quality monitoring. However, there are several vulnerabilities such as human error, technical issues with the ERP system, and weather-related delays in shipping raw materials. Recommended improvements include improved employee training, optimizing the ERP system, and developing more efficient inventory management. This research provides insights into the importance of evaluating accounting systems to improve the efficiency and effectiveness of business operations. Further research is recommended to conduct comparative analysis with other companies and explore new technologies to increase purchasing management transparency and efficiency